Health Belief Model on the Influence of Personal and Work Factors on the Perception of Low Back Pain - Saifudin Zuhri; Sri Suwarni (Poltekkes Kemenkes Surabaya, 2024)
The prevalence of low back pain (LBP) in Indonesia is increasing with age and deviant behavior in the workplace. If people are not aware of the vulnerability they feel, it can lead to deformities and disabilities as perceived severity. So that behavior changes with motivation for public health. This study aims to analyze the relationship between personal and work factors and the perception of LBP. This type of research is a cross sectional quantitative research. The research location is in Sukoharjo, Central Java. The sampling technique was purposive non-random sampling with a total sample of 120 respondents. Data were collected using questionnaires, then analyzed using multiple linear regression tests. The results of bivariate analysis showed that personal factors had a positive and significant correlation with the perception of LBP incidence (r=0.549, p<0.001). Occupational factors had a positive and significant correlation with the perception of LBP incidence (r = 0.680, p<0.000). Personal and occupational factors simultaneously affected the perception of LBP incidence with a p value of 0.000 and the contribution of these two variables to the perception of LBP incidence was 48.3%. It can be concluded that both partially and simultaneously, personal and occupational factors affect the perception of LBP incidence. Suggestions for further research are needed to explore other factors that influence the perception of LBP events. This is important to deepen understanding of the various aspects that can affect an individual's perception of LBP, including environmental, psychosocial, and lifestyle factors.